Biodegradable antenna on fiber-based substrate - Tan, Yun Xian (2018)
With the increase in demand for better healthcare, large amounts of money are being devoted to improve and create new kinds of Implantable Medical Devices (IMDs). The greatest challenge facing the healthcare industry is the ability to create more and better healthcare equipment so as to cope with the ageing population and the rise of new kinds of viruses and illnesses. In this project, studies were done to determine whether a newly proposed prototype is a viable option as an IMD. The prototype is an antenna printed on a biodegradable substrate, poly(l-lactide-co-ε-caprolactone) (PLC). The ink used to print the antenna will be carbon nanotube (CNT) ink. The mechanical and electrical properties of the prototype were investigated in this project. Tensile tests on the prototype proved that it is elastically compatible in the body and conductivity tests proved that electricity could pass through the circuit. Also, tests were carried out to determine if there was a relationship between the resistance of the circuit and the number of layers of circuit printed. It has been found that as the number of layers increased, the resistance of the circuit decreased. The results obtained through these experiments verified that this prototype could be used as an IMD and further research such as the biocompatibility of the ink should be done to further prove if it is a viable option as an IMD. This will be a stepping-stone to future research, which if successful, will be beneficial to the healthcare industry.